Oxidative stress in rat liver during acute cadmium and ethanol intoxication - Radosavljević Tatjana; Mladenović Dušan; Ninković Milica; Vučević Danijela; Boričić Ivan; Ješić-Vukićević Rada; Šljivančanin Tamara; Lopičić Srđan; Todorović Vera (Journal of the Serbian Chemical Society, 2012)
The aim of our study was to investigate the effects of binge drinking on prooxidant/antioxidant system in rat liver in acute cadmium (Cd) intoxication. In experiment male Wistar rats were used and divided into following groups: 1. control, 2. ethanol-treated group, in five subsequent doses of 2 g/kg administered by orogastric tube, 3. Cd-treated group in a single dose of 2.5 mg/kg intraperitoneally, 4. group that received Cd 12 hours after the last dose of ethanol. Blood and liver samples were collected for determination of oxidative stress parameters, 24 hours after treatment. When administered in combination, ethanol and Cd induced a more pronounced increase in serum and liver malondialdehyde level than either of these substances alone (p<0.01). Liver manganese superoxide dismutase (MnSOD) activity was increased both in ethanol and Cd-treated group (p<0.01), while liver copper/zinc superoxide dismutase (Cu/ZnSOD) activity was elevated in Cd group only. However, when administered in combination, ethanol and Cd induced a more pronounced decrease in liver MnSOD and Cu/ZnSOD activity 24 hours after treatment (p<0.01). Based on our study, it can be concluded that ethanol may act sinergistically with Cd in inducing lipid peroxidation and reduction in liver SOD activity.